Superconductivity in a new layered triangular-lattice system Li2IrSi2. (24th September 2019) - Horigane, K; Takeuchi, K; Hyakumura, D; Horie, R; Sato, T; Muranaka, T; Kawashima, K; Ishii, H; Kubozono, Y; Orimo, S; Isobe, M; Akimitsu, J
Abstract: We report on the crystal structure and superconducting properties of a novel iridium-silicide, namely Li2 IrSi2 . It has a Ag2 NiO2 -type structure (space group R-3m) with the lattice parameters a  = 4.028 30(6) Å and c  = 13.161 80(15) Å. The crystal structure comprises IrSi2 and double Li layers stacked alternately along the c -axis. The IrSi2 layer includes a two-dimensional Ir equilateral-triangular lattice. Electrical resistivity and static magnetic measurements revealed that Li2 IrSi2 is a type-II superconductor with critical temperature ( T c ) of 3.3 K. We estimated the following superconducting parameters: lower critical field H c1 (0) ∼ 42 Oe, upper critical field H c2 (0) ∼ 1.7 kOe, penetration depth λ 0  ∼ 265 nm, coherence length ξ 0  ∼ 44 nm, and Ginzburg–Landau parameter κ GL  ∼ 6.02. The specific-heat data suggested that superconductivity in Li2 IrSi2 could be attributed to weak-coupling Cooper pairs.